Improving Graduate Quality through Networked Curriculum Integration in Madrasahs Using the ABCD Method - Yusuf Yusuf; Wati Karmila; Ade Aspandi (Journal of General Education and Humanities, 2026)
This community service study addresses the need to strengthen graduate quality in Islamic educational institutions facing contemporary challenges such as globalisation, cultural transformation, and moral development. The study aims to examine how integrating a networked curriculum model can support the development of graduate quality in State Tsanawiyah Madrasah (MTsN 2 Ciwaringin) and State Aliyah Madrasah (MAN 2 Ciwaringin) located in Babakan Ciwaringin, Cirebon. The research applies the Asset-Based Community Development (ABCD) approach, focusing on identifying and utilising existing institutional and community assets. The activities were conducted through mentoring, discussions, and collaborative sessions involving teachers as the main participants. Data were collected through observation, documentation, and discussion results, and were analysed descriptively to capture institutional processes and teacher engagement during the program. The findings indicate that both madrasahs demonstrate strong institutional assets, including qualified teachers, supportive learning environments, and connections with surrounding Islamic boarding schools. The integration of the networked curriculum model, implemented through participatory and collaborative processes, strengthens curriculum practices, teacher involvement, and institutional coordination. In addition, internal quality control mechanisms led by madrasah leadership were observed to support the implementation of curriculum integration. These findings are based on teacher participation, institutional processes, and descriptive evaluation rather than direct measurement of student outcomes. The study suggests that integrating a networked curriculum model through the ABCD approach provides a structured framework that supports the development of educational practices and graduate quality in madrasah contexts.